Gender Difference and Levels of Requirement for Information Resources and Services of the Career Seekers in Kerala - DINESHAN KOOVAKKAI and JALAJA V (LIBRARY HERALD, 2006)
The problem of educated unemployment is a crucial social problem in Kerala. As the educational status of women is comparatively high in the state, it is worthwhile to study how far the requirement level of the female career seekers is different from that of the male career seekers. The data were collected using questionnaire from 1180 career seekers out of which 1039 respondent. The study reveals that no much difference exists between the male and the female career seekers in Kerala in the level of requirement for majority of the resource and services. However the requirement level of the female career seeker is higher in the cases where difference is observed.